Analysis of Epidemiological Situation on Crimean Hemorrhagic Fever in the Russian Federation in 2013 and Prognosis for 2014 - A. S. Volynkina; N. D. Pakskina; E. V. Yatsmenko; E. S. Kotenev; Ya. V. Levantzova; O. V. Maletskaya; L. I. Shaposhnikova; Yu. M. Tokhov; A. N. Kulichenko (Проблемы особо опасных инфекций, 2014)
Crimean hemorrhagic fever remains one of the priority infections in the South of Russia. Within the past five years morbidity rates are retained consistently high in a number of regions; mortality rates are on average 4.4 %. In 2013 registered were 79 cases of CHF in the Southern and North-Caucasian Federal Districts. Therewith performed has been analysis of epidemiological situation on CHF in the Russian Federation for 2013, summarized have been the results of epizootiological surveillance of the natural CHF focus area in the South of European Russia, discussed are the results of genetic CCHF virus typing, identified in 2011-2013 in the South of Russia. Based on epizootiological surveillance data made has been the forecast of epidemiological situation development as regards CHF for 2014.